2021
DOI: 10.3390/pharmacy9030115
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Frail Older Patients: Glycemic Control and Prescription Profile in Real Life

Abstract: (1) Background: The latest recommendations for diabetes management adapt the objectives of glycemic control to the frailty profile in older patients. The purpose of this study was to evaluate the proportion of older patients with diabetes whose treatment deviates from the recommendations. (2) Methods: This cross-sectional observational study was conducted in older adults with known diabetes who underwent an outpatient frailty assessment in 2016. Glycated hemoglobin (HbA1c) target is between 6% and 7% for nonfr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…In routine clinical practice, even in specialist centres, frailty still does not seem to be taken into consideration when deciding on diabetes management, glycaemic control and HbA1c targets [ 140 , 141 ]. We have demonstrated that frailty is a complex metabolic condition with a spectrum of metabolic phenotypes with variation in insulin sensitivity that may affect the choice of hypoglycaemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In routine clinical practice, even in specialist centres, frailty still does not seem to be taken into consideration when deciding on diabetes management, glycaemic control and HbA1c targets [ 140 , 141 ]. We have demonstrated that frailty is a complex metabolic condition with a spectrum of metabolic phenotypes with variation in insulin sensitivity that may affect the choice of hypoglycaemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we defined HbA1c level ≥6.5% as high HbA1c levels. In elderly and frail diabetic patients, it is recommended to set higher HbA1c thresholds than in young patients [21,22]. Therefore, separate HbA1c cutoffs for different age groups may be more appropriate [22].…”
Section: Discussionmentioning
confidence: 99%
“…We assessed 98 full-text articles for inclusion and identified 11 studies that met our inclusion criteria. [19][20][21][22][23][24][25][26][27][28][29] two were cross-sectional studies 19,20 with a mix of prospective [19][20][21][22][23][24][25] and retrospective 19,21,25 studies. One study was post-hoc analysis of a large randomised controlled trial.…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…26 A range of care settings were included with 6 studies 20,21,[24][25][26]29 from primary care settings, 4 from hospital inpatients [22][23][24]27 and 1 from a hospital outpatient department. 19 Studies were from a wide range of geographical locations 3 from the USA, 25,27,28 with 2 each from Italy, 20,24 Spain 21,22 and 1 each from the UK 23 Australia, 26 France 19 and the Netherlands. 29 Four studies specifically related to type 2 diabetes, 21,23,26,27 with the others only specifying a general diabetes diagnosis rather than type of diabetes.…”
Section: Re Sults and Discussionmentioning
confidence: 99%